Perspective of Lecturers in Implementing PISMP Science Curriculum in Malaysia’s IPG - Fauziah Hj Yahya; Abdul Rahim Bin Hamdan; Hafsah Binti Jantan; Halimatussadiah Binti Saleh (International Journal of Evaluation and Research in Education (IJERE), 2015)
The article aims to identify lecturers’ perspectives in implementing PISMP science curriculum in IPG Malaysia based on teaching experience with KIPP model. The respondents consisted of 105 lecturers from 20 IPG Malaysia. The study used a questionnaire consisting of 74 items covering the four dimensions (Context, Input, Process and Product). Data collected through questionnaires were analyzed using one-way ANOVA. The study found that there was not a significant difference of curriculum goals and course objectives based on teaching experience at school. For input dimension, there was no significant difference of evaluation, content, source and pedagogy based on school teaching experience. In process dimension, there was no significant difference pedagogical process, the content and the process of assessment based on teaching experience at school. Furthermore, there was no significant difference of product dimension of science curriculum based on teaching experience at school. Based on the experience of teaching in IPG, lecturers did not have a significant difference of curriculum goals, course objectives, evaluation input, content, source, pedagogy, and evaluation process, and content process, but there were significant differences in the pedagogical input and product in the implementation of the PISMP science curriculum in IPG. Its discussions and recommendation were also discussed in this article.